Absolute magnetic susceptibility of rat brain tissue. Issue 3 (7th October 2013) - Peprah, Marcus K.; Astary, Garrett W.; Mareci, Thomas H.; Meisel, Mark W.
<x xml:space="preserve">Abstract</x> Purpose This study was performed to test the commonly held hypothesis that the absolute magnetic susceptibility of brain tissue is close to that of water since water accounts for over 50% of the tissue composition. In addition, the absolute value of susceptibility of brain tissue is needed for the development of materials that are implanted into or in close proximity to tissue. Methods The absolute magnetic susceptibilities of different sections of rat brain, which were exsanguinated and perfusion‐fixed, have been measured in a commercial superconducting quantum interference device magnetometer operating in fields up to 7T. Results The average measured values ranged from −(9.51 ± 0.01) × 10−6 for the cerebellum to −(8.99 ± 0.01) × 10−6 for a mixture of hippocampus, corpus callosum, and striatum. The time evolution of the samples was also studied, and deviations of <1% were observed after 4 weeks, although this trend was sample‐specific. Conclusion The measured susceptibilities are close to the value measured for high‐performance liquid chromatography H2O and depend on the amount of gray and white matter regions present in the samples. Magn Reson Med 72:876–879, 2014. © 2013 Wiley Periodicals, Inc.